2016
DOI: 10.1039/c6cp06788c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cycling durability of Li-ion batteries with hierarchical structured silicon–graphene hybrid anodes

Abstract: Copies of full items can be used for personal research or study, educational, or not-for-profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. Publisher statement:First published by Royal Society of Chemistry 2016 http://dx.doi.org/10.1039/C6CP06788C A note on versions:The version presented here may differ from the published versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…It indicates that by incorporating FLG, the “roll-over” effect is significantly delayed, possibly due to the enhanced tensile properties from the FLG (Supplementary Figure 1 ), which reduces the rate of the pulverization of the electrode microstructure. When referring to the previous Si-FLG study 14 , which demonstrated about 200 cycles under the capacity 1800 mAh/g, it can be concluded that 16% FLG in this formulation is a more effective ratio.
Figure 2 ( a ) Half-cell cyclability and ( b ) columbic delithiation efficiency under capacity limitation of 1800 mAh/g for Si-FLG formulation matrix (Formula A – 76% Si: 0% FLG: 12% Na-PAA: 12% Carbon.
…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…It indicates that by incorporating FLG, the “roll-over” effect is significantly delayed, possibly due to the enhanced tensile properties from the FLG (Supplementary Figure 1 ), which reduces the rate of the pulverization of the electrode microstructure. When referring to the previous Si-FLG study 14 , which demonstrated about 200 cycles under the capacity 1800 mAh/g, it can be concluded that 16% FLG in this formulation is a more effective ratio.
Figure 2 ( a ) Half-cell cyclability and ( b ) columbic delithiation efficiency under capacity limitation of 1800 mAh/g for Si-FLG formulation matrix (Formula A – 76% Si: 0% FLG: 12% Na-PAA: 12% Carbon.
…”
Section: Resultsmentioning
confidence: 72%
“…A previous study on these systems has reported that interconnecting few-layer graphene (FLG) with Si can be an effective solution to enhance the cycling stability through the formation of a conductive, hierarchical structure 14 . This approach was adopted in this study and all electrodes were manufactured with a relatively high mass loading of micron-sized silicon particles using mechanical dispersion apparatus aligned with industrial electrode fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…9(b) the initial lithiation of crystalline bulk silicon results in a low voltage plateau corresponding to a two-phase region in which lithiated amorphous silicon is formed (a-Li x Si). 54,55 Limiting the capacity to around 1000 mA h g À1 will avoid the deleterious volume expansion, which occurs when the highest lithiated Si species Li 15 Si 4 is formed through recrystallisation. This phase formation is associated with an entire amorphous to crystalline transformation, whose onset occurs at around 60 mV and continues when the voltage < 50 mV.…”
Section: Resultsmentioning
confidence: 99%
“…The final aim would be that of providing a comprehensive tool to refer to in order to systematically evaluate and critically asses each new sodium-ion fullcell chemistry proposed in the literature, in order to probe its technological readiness level. Recently the research around high capacity anodes for SIBs (based on 14th and 15th group elements alloys or oxide based conversion materials) has been knowing a positive momentum, thanks to the hype also deriving from lithium-rich full battery counterpart (silicon [67,68] and sulfur [69] based LIBs). Not all the applications field would work for a sodium-ion technology.…”
Section: Full-cell Preparation Challengesmentioning
confidence: 99%
“…The full-cell delivers an average operating voltage plateau at 2.53 V and extraordinary rate and superior cycling performance. 67 Ni 0.33 O 2 [317] and Na 0. It was demonstrated that this cation-disordered material can function as both positive and negative electrodes with average operation voltages of 3.5 and 0.8 V, corresponding to the RedOx couples Cr 4+ / Cr 3+ and Ti 4+ /Ti 3+ , respectively.…”
Section: Sodium-ion Full Battery Based On Layered Oxidesmentioning
confidence: 99%